2016
DOI: 10.1002/erv.2494
|View full text |Cite
|
Sign up to set email alerts
|

Threat‐Detection and Attentional Bias to Threat in Women Recovered from Anorexia Nervosa: Neural Alterations in Extrastriate and Medial Prefrontal Cortices

Abstract: Women recovered from AN are characterized by altered neural responses to threat cues. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…As REC did not show behavioural differences compared with NP, this neural signature might resemble a trait-phenomenon. Similar phenomena, that is, discrepancies of behavioural and neural data, were obtained in threat-detection, attentional bias to threat, and emotional conflict in REC (Bang et al, 2016(Bang et al, , 2017.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As REC did not show behavioural differences compared with NP, this neural signature might resemble a trait-phenomenon. Similar phenomena, that is, discrepancies of behavioural and neural data, were obtained in threat-detection, attentional bias to threat, and emotional conflict in REC (Bang et al, 2016(Bang et al, , 2017.…”
Section: Discussionsupporting
confidence: 64%
“…This resulted from a deceased recruitment in NP in combination with an increased recruitment in the AN group. Furthermore, studies of REC by Bang et al on socioemotional processing (threat detection and emotional conflict) yielded similar phenomena of decreased modulation (Bang, Rø, & Endestad, , ). Looking at recent studies evaluating disorder‐specific paradigms (food images), it seems that there is preserved modulation (Oberndorfer et al, ; Sanders et al, ; Scaife, Godier, Reinecke, Harmer, & Park, ).…”
Section: Discussionmentioning
confidence: 71%
“…Hyperactivation of extrastriate visual areas in OB patients, and increased connectivity of this region with other high-order visual processing areas, could be indicative of diminished control in the visual regions while processing emotionally salient stimuli 59 . In this sense, bidirectional feedback connections between the amygdala and extrastriatal visual areas are involved in the perceptual enhancement of emotionally relevant stimuli 60 and failure to properly engage this visual processing stream is likely to underlie in some measure the attentional biases found in OB 6062 . Importantly, activation in the extrastriate visual cortex during emotion regulation was positively associated with body fat percentage in the control group, which indicates that increased activation of this region is not exclusively observed in obese individuals but also in those lean controls with a higher body fat percentage.…”
Section: Discussionmentioning
confidence: 99%
“…AN participants displayed elevated activity in the bilateral fusiform gyri for self-images, unlike the weight-recovered and healthy women, leading the authors to suggest cognitive distortions about physical appearance are a state rather than trait feature in AN [114]. However, one recent study identified persistent hyperactivation in the medial PFC during attentional bias to angry faces in recovered AN patients [115], possibly reflecting the existence of compensatory mechanisms. Lastly, abnormal spatiotemporal activation also appear to persists after recovery in AN, with one study identifying alterations in configural/holistic information for appearance- and non-appearance-related stimuli processing in patients with body dysmorphic disorder (BDD) and weight-restored AN patients [116].…”
Section: Self-monitoring Networkmentioning
confidence: 99%